2022
DOI: 10.25082/amler.2022.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Digital activism in students of a university in central Mexico in the COVID-19 era

Abstract: The exploration of the dimensions of digital activism was the aim of this work. The first and second non-experimental studies were carried out with a non-probabilistic selection of 100 students, considering their affiliation with student organizations. A four-dimensional structure was set up; technological habitus, computational self-efficacy, diffusion of innovations, and Internet mobilization explained 48% of the total variance, although the design limited the results to the research scenario, suggesting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 65 publications
1
34
0
Order By: Relevance
“…Although the importance of learning and teaching in the content of IM has drawn significant scientific attention over the last years, very few studies were found to focus on interventional studies and their effectiveness (Aguayo et al, 2022;Mohammed, 2022). Specifically, studies that use quantitative data or assess the impact of an educative education on students learning and IM competencies are scarce, and teachers are neglected.…”
Section: Discussionmentioning
confidence: 99%
“…Although the importance of learning and teaching in the content of IM has drawn significant scientific attention over the last years, very few studies were found to focus on interventional studies and their effectiveness (Aguayo et al, 2022;Mohammed, 2022). Specifically, studies that use quantitative data or assess the impact of an educative education on students learning and IM competencies are scarce, and teachers are neglected.…”
Section: Discussionmentioning
confidence: 99%
“…Rais et al (2018) explain that game-based learning could attract learners to play the game and learn. This state makes learners memorize and retain it longer because it involves cognitive, affective, psychomotor, emotional, and social skills (Aguayo et al, 2022). Khotima & Pratama (2022) explain that an educative game makes learners more active.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…The most important aspect of this kind of activity would be the fairness with which one student marks, comments, and provides feedback to others. Teachers are allowed to disclose their students' grades only when it is necessary to do so (Aguayo et al, 2022;Can & Bardakci, 2022).…”
Section: Students and Teachers' Experiencesmentioning
confidence: 99%